KEWAJIBAN VERSUS MORALITAS DALAM "ANTIGONE" KARYASOPHOCLES - Syam, Essy (Jurnal Ilmu Budaya, 2015)
This writing deals with a dilemma faced by Antigone on deciding what to do in response to the kings decision not to bury her brothers dead body or following her morality and conscience to conduct a burial of the brothers dead body. She finally decides to bury the dead body and face the consequence of the kings anger. As a result she has to face the punishment from the king. This writing shows that when morality guides someone, s!he should be ready to accept any consequence. Antigone s decision to oppose the king shows that obligation to obey the king is not always parallel with morality and her conscience.